2016
DOI: 10.3136/fstr.22.317
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Liquid and Solid Seasonings with Shrimp-like Flavor from Isada Krill under Subcritical Water Conditions by Steam Injection

Abstract: Isada krill (12.5 kg) was first treated under subcritical water conditions at 140℃ or 160℃ by injecting steam into a large pressure-resistant vessel, and it was then separated into liquid extract and solid residue. The solid content, salt concentration, protein content, antioxidative activity, and odor intensity of the extract, as well as the color and odor of the residue, were determined. The preference score and flavor characteristics of both the extract and the residue were assessed by sensory evaluation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Because of these characteristics, subcritical water has attracted a signifi-cant amount of attention as a reaction solvent and extractant. We have previously reported that the treatment of Isada krill [8][9][10][11][12] or its residual waste solution [13] under subcritical water conditions at 140 to 200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these characteristics, subcritical water has attracted a signifi-cant amount of attention as a reaction solvent and extractant. We have previously reported that the treatment of Isada krill [8][9][10][11][12] or its residual waste solution [13] under subcritical water conditions at 140 to 200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the treatment of Isada krill [6][7][8][9][10], or that of its residual waste solution [11], under subcritical water conditions at 140-200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have reported that the extracts and solid residues obtained from subcritical water treatment of Pacific krill can be used as a food ingredient (Koomyart et al 2015a, b, 2016Tamiya et al 2016. However, color changes in the extract and solid residue during the subcritical water treatment have never been studied despite the fact that color is a very important factor influencing the acceptance of a product.…”
Section: Introductionmentioning
confidence: 99%